Profiling the resiliency and sustainability of UK manufacturing companies. Issue 1 (1st February 2016) - Thomas, Andrew; Byard, Paul; Francis, Mark; Fisher, Ron; White, Gareth R.T.
Abstract : Purpose: – The purpose of this paper is to identify the tools, methods and models that UK manufacturing companies adopt and apply in order to achieve resiliency and economic sustainability. The results of this work can assist in developing the foundations for defining a new joint resiliency/sustainability paradigm to assist industry. Design/methodology/approach: – Through a detailed, triangulated secondary data analysis and industry survey, the authors initially identify and then analyse the key resiliency and sustainability characteristics surrounding manufacturing operations. This paper initially reviews key literatures around resiliency and sustainability models and frameworks and subsequently draws out their key features and weaknesses. The work then details the research survey undertaken in to manufacturing companies aimed at identifying the resiliency/sustainability approaches that are adopted in companies. A sample of 72 manufacturing companies are used in the survey and from which the results are based. Findings: – Through analysing the fundamental business data of sales and manufacturing costs for 72 manufacturing companies, the authors cluster the companies in to four key manufacturing profiles. The work then shows through a more detailed analysis of the profiles that companies which are sustainable and more resilient in nature are, better engaged and connected to the development and application of resiliency and sustainability models. It was found that companies who seem to struggle in achieving economic sustainability or lack the ability to bounce back from various set-backs either do not employ such models or at best apply tools and techniques in an ad hoc manner. Research limitations/implications: – The paper provides key insights in to the adoption of tools, techniques and models surrounding the achievement of resiliency and sustainability in manufacturing companies. In so doing, the paper offers a new view on these issues and with the profiling exercise undertaken, companies will be able to identify their position in relation to the survey companies. This can be of benefit to the wider industrial and academic community. The development of a qualitative assessment around a relatively small sample size has its obvious limitations and it is crucial that further work with a range of companies in the area of manufacturing sustainability is key to developing (and also validating) a comprehensive set of resiliency and sustainability characteristics. Practical implications: – The paper highlights the issues surrounding existing academic resiliency/sustainability models and through the industry survey, it provides further information on where UK manufacturing companies are on adopting specific resiliency/sustainability models. The work suggests that the resiliency/sustainability landscape of UK manufacturing companies is much more complex and that a single strategic approach towards achieving improved manufacturing performance is somewhat dated and ineffective. Originality/value: – The development of a set of resiliency/sustainability profiles including the identification of the specific tools and techniques adopted by industry is aimed at tackling directly the issues of improving company performance and is considered by the authors as one of a kind. The results of the survey provide essential information on the resiliency/sustainability landscape of UK manufacturing companies.